Automatic allocation of resources in software process simulations using their capability and productivity. Issue 3 (1st August 2016) - Kuchař, Š; Vondrák, I
Abstract: Software processes are very dependent on human behaviour, creativity and productivity. Business process management (BPM) simulation models are trying to model these properties to provide more precise information about the progress and parameters of the process. This paper describes a method for specifying competencies of resources in the process using competency models. These competencies are used to simulate human resource capability and productivity that influences the duration and allocation of resources to activities in the process. Different allocation strategies are based on this capability and productivity model to determine which resources should be allocated during automatic simulations. This method is then integrated into the BPM method simulation environment that is used to compare these allocation strategies in software process simulations for a middle-sized software development company.